PERISTIWA BERDARAH DI PULAU GADANG KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR TAHUN 1949 - Restu Wulandari; Ridwan Melay; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Bloody event in the village of Pulau Gadang, which was then led by colonel Hoemala Silalahi as a reaction to the Dutch 2nd Military Agression launched on 4 March 1949. Making troop i succed in countinuing the leadership of the Republik Indonesia. In its pursuit of the Kampar Watershed incluiding in the Village of Pulau Gadang wich was the main destination of the Netherlands. The purpose of this study is 1) To know the condition of the village of Pulau Gadang before the occurrence of a bloody event, 2) To know the background of the occurrence of bloody events in the village of Pulau Gadang, 3) To know how there was a bloody event in the village of Pulau Gadang, 4) To know the consequence of bloody events in the island of Pulau Gadang, 5) To know how people remember the bloody events in the village of Pulau Gadang. The research uses qualitative research methods with historical (History) and data collection techniques in the from of bibliography, documentation, observation, and interview. The result is the resistance made by Pulau Gadang society to make the Dutch angry and burn almost all building in Pulau Gadang as well as killing severall warriors in village. So great the sacrifices and struggles that nation been passed by the heroes of the nation, thus we should as the next generation of the nation to always remember and appreciate the service of the heroes and not forget any historical that in this country.Key Words: Bloody Events In The Village Of Pulau Gadang Subdistrict XIII Koto Kampar, Kampar District Years 1949.